Evaluating the design features of Islamic website: a Muslim user perception - Aliyu, Mansur; Mahmud, Murni; Md Tap, Abu Osman (2013)
Website design features have been widely studied by researchers in various fields most especially in e-commerce. Indeed, website design features are widely regarded as vital tools that influence website use. However, few studies devoted significant attention on Islamic website design features that influence website use. The purpose of this study is to identify and explore the most important design features of Islamic websites that influence website use. The study conducted a content analysis on some selected Islamic website studies where 86 design features were identified, selected, modified, and categorized around 6 broad features (factors). Furthermore, an online survey of 89 Muslim users of Islamic websites was conducted to rank the identified design features in terms of their importance to the users. The findings of the exploratory factor analysis provide evidence to suggest that only few design features are considered important by Islamic website users. These design features possess high significant factor-loading and are grouped under “functionality”, “navigation”, “interactivity”, “attractiveness”, “organization”, and “security/privacy”. The study found the above design features to be significant in influencing Islamic website use.